DESAIN INTEGRASI PENDIDIKAN KARAKTER KE DALAM PEMBELAJARAN PKn POKOK BAHASAN PELAKSANAAN DEMOKRASI DALAM BERBAGAI ASPEK KEHIDUPAN KELAS VIII DI MTs NEGERI BARAMBAI - Joko Wiyono (JURNAL SOCIUS, 2013)
Based on the observation in MTs Negeri Barambai Barito Kuala, integrating education character into democracy topic in any kinds of life is not developed and implimented maximally. Because there is no integrated learning design and teacher’s capability to inovate in learning, this research has the objective to create design of education character integrated into citizen  education for the topic ‘democracy’ in any kinds of life for eighth class. This research used the qualitative approach by getting the data descriptively whether in written or behavior observed. The step used in this research was adopted from the Suheri’s research design that follows the steps of Broug’s and Gall’s research. This research is also based on the steps as guide form Direktorat Pendidikan SMP Kemdikbud 2010 in integrating character education into citizen education. The research result is a model of integrated design of character education into citizen education.  Key words: Integrated Design, Character Education, Citizenship Education, and Democracy